Mitochondrial dysfunction in non-alcoholic fatty liver disease and insulin resistance: Cause or consequence?. (November 2013) - García-Ruiz, C.; Baulies, A.; Mari, M.; García-Rovés, P. M.; Fernandez-Checa, J. C.
Abstract Non-alcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of the metabolic syndrome and refers to a spectrum of disorders ranging from steatosis to steatohepatitis, a disease stage characterized by inflammation, fibrosis, cell death and insulin resistance (IR). Due to its association with obesity and IR the impact of NAFLD is growing worldwide. Consistent with the role of mitochondria in fatty acid (FA) metabolism, impaired mitochondrial function is thought to contribute to NAFLD and IR. Indeed, mitochondrial dysfunction and impaired mitochondrial respiratory chain have been described in patients with non-alcoholic steatohepatitis and skeletal muscle of obese patients. However, recent data have provided evidence that pharmacological and genetic models of mitochondrial impairment with reduced electron transport stimulate insulin sensitivity and protect against diet-induced obesity, hepatosteatosis and IR. These beneficial metabolic effects of impaired mitochondrial oxidative phosphorylation may be related not only to the reduction of reactive oxygen species production that regulate insulin signaling but also to decreased mitochondrial FA overload that generate specific metabolites derived from incomplete FA oxidation (FAO) in the TCA cycle. In line with the Randle cycle, reduced mitochondrial FAO rates may alleviate the repression on glucose metabolism in obesity. In addition, the redox paradox in insulin signaling and the delicate mitochondrial antioxidant balance in steatohepatitis add another level of complexity to the role of mitochondria in NAFLD and IR. Thus, better understanding the role of mitochondria in FA metabolism and glucose homeostasis may provide novel strategies for the treatment of NAFLD and IR.